Ta’lim lughah al Arabiyah an Bu’din bi Wasitotil Whatsapp Bi Jami'ati Ifriqiya Al 'Alamiyah - Najmuddin, Muhammad; Saedeh, Mariam; Zainal Abidin, Ahmad; Sunarko, Asep; Rehab, Rehab; Muna, Umi Kultsum Qothrotul; Alfarizi , Saif Alif (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
This study explores the use of the WhatsApp application in online Arabic language learning at the International University of Africa in Sudan during the armed conflict in the country. This qualitative case study investigates how WhatsApp was utilized as a distance learning medium to maintain the continuity of education amidst the crisis. Through observations and analysis of WhatsApp conversations, the research reveals challenges such as internet connection issues, limitations of the app's features, and a decline in students' learning motivation. However, the instructors endeavored to overcome these obstacles by employing various strategies, such as using voice notes, sharing materials in document form, conducting scheduled discussion sessions, and collaborating with students with better internet access. Although WhatsApp is not a platform designed specifically for learning, the study finds that the application can be an effective solution for distance learning in emergency situations, while continuing to explore more comprehensive alternatives for the future.